A short history of flexible hours - historical baselines of working time policy in Germany - Markus Promberger (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2021)
This paper analyses the structures and patterns, dimensions and interest relations behind 200 years of working time negotiations and conflicts, based on historical and contemporary literature and research, mainly but not exclusively in Germany. One main thesis is that 'new' flexibilization trends are not new at all, while the effective standardization of working hours is limited to a couple of decades in the 20th century. Nevertheless and for various reasons, working time arrangements are a social and political issue which should not be left to individual contracting but subject to reflexive labour policy. – – Dieses Papier analysiert die Strukturen, Muster, Dimensionen und Interessen von 200 Jahren Arbeitszeitpolitik, vor allem in Deutschland. Auf der Grundlage historischer und aktueller Literatur wird die These belegt, dass scheinbar neue Trends der Flexibilisierung von Arbeitszeiten alles andere als neu sind, wenn man den historischen Untersuchungszeitraum ausweitet. Vielmehr beschränkt sich die Phase einer tatsächlichen Standardisierung von Arbeitszeiten auf wenige Jahrzehnte des zwanzigsten Jahrhunderts. Gleichwohl und sinnvollerweise bleiben Arbeitszeitarrangements ein Gegenstand sozialer und politischer Auseinandersetzung. Sie sollten nicht den einzelnen Arbeitsverträgen überlassen bleiben sondern Gegenstand reflexiver Arbeitszeitpolitik sein.
Keywords: J22; J50; N30; N33; N35; O35; O52; 330; collective bargaining; individual preferences; industrial relations; labour history; welfare capitalism; working hours; working time; working time policies